Preferential Trade Agreements as Stumbling Blocks for Multilateral Trade Liberalization: Evidence for the United States - Limão, Nuno (American Economic Review, 2006)
Most countries are members of preferential trade agreements (PTAs). The effect of these agreements has attracted much interest and raised the question of whether PTAs promote or slow multilateral trade liberalization, i.e., whether they are a “building block” or “stumbling block” to multilateral liberalization. Despite this long-standing concern with PTAs and the lack of theoretical consensus, there is no systematic evidence on whether they are actually a stumbling block to multilateral liberalization. We use detailed data on U.S. multilateral tariffs to provide the first systematic evidence that the direct effect of PTAs was to generate a stumbling block to its MTL. We also provide evidence of reciprocity in multilateral tariff reductions.